Development of Biology Learning Media Based on Android to Improve Students Understanding - Lufty Hari Susanto; R. Teti Rostikawati; Rahmi Novira; Rika Sa'diyah; Istikomah Istikomah; Ilmi Zajuli Ichsan (Jurnal Penelitian Pendidikan IPA, 2022)
This study aims to development of media mobile learning based on android for learning the biology of nervous system material and to determine the effectiveness of media mobile learning based on android in improving students' conceptual understanding. The type of research used was development (R&D), population, and sample, namely class XI IPA 2 as many as 30 students at one of the public high schools in Bogor Regency which was carried out from January to May 2020. This development research procedure used a model (4D) consisting of 4 stages, namely Define, Design, Develop, and Disseminate. The instruments   used   were   tests (pre- test and post-test), response questionnaire sheets, and documentation. The implementation of deployment trials was carried out using a one group pre-test and post-test research design. The results showed that the media mobile learning got a very feasible category. This is based on the average percentage of the assessment from the expert validation team, namely 82.75%. Media mobile learning Android-based on learning the biology of the nervous system material can improve students' understanding of concepts and almost all students respond positively. This is proven by an increase in the results of the pre-test and post-test values after using the application so that the N-gain value obtained is 66.5.